The Scepticism of Descartes’s Meditations - Thomas, James (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2011)
What I’m suggesting is that the model for Descartes’s defence of Renaissance science would be Aquinas’s own defence of thirteenth-century Aristotelian science, except that the coherence of the will took on the role of the consistency of concepts, as the controlling factor in the analyses of all types of science. As a result, the new science would incorporate the awareness of Platonic ideas and the divisibility of Euclidean space as equally valid input into a dialectical knowledge of sensory experience. You can read the early arguments to doubt the reality of sensory experience and reason as a way of dividing out the experience of the will in affirming or denying an object’s nature, as the subject for subsequent inquiry.